Virtual reality in post-stroke upper limb rehabilitation: serious games using hand tracking - Silva, Ricardo Jorge Freitas (2018)
In recent years, Virtual Reality has been shown to have considerable potential as a rehabilitation tool, as it allows the creation of Virtual Environments providing multiple stimuli that can motivate, engage or distract the patients. Moreover, VR applications may meet the four basic principles of rehabilitation: intensity, task oriented training, biofeedback and motivation, all pivotal factors for the success of rehabilitation programs. Aware of this potential, and concerned with the lack of motivation of stroke patients while performing repetitive upper limb movements, a group of professionals working at a national rehabilitation center contacted the university to develop VR games aimed at increasing motivation by providing everyday life context to the movements. This dissertation establishes the initial iteration towards the addition of VR to the occupational therapy routine in the rehabilitation center, including the assessement of requirements for the applications to be developed, establishment of the system architecture, development of rehabilitation game prototypes and integration with a backend database server and a configuration web page. The work was concluded with a formal usability and satisfaction study with patients residing at the rehabilitation center.